Autoimmune hepatitis with overlap of primary biliary cirrhosis as the cause of esophageal varices in a geriatric patient, case report. - Martha A. López-Hernández; José A. Novoa-Búrquez; Vanessa Camacho-García; Alma E. Enríquez-Valeriano; Francisco A. Félix-Téllez; Juan M. Díaz-Castillón; Daniela G. Fausto-Murillo; Margarita Ortiz; Santos González-Luna; Diego A. Zúñiga-Tamayo; Héctor I. Cruz-Neri (Annals of Hepatology)
Introduction and Objectives: A case is presented of an elderly female patient, without risk factors or comorbidities, who debuts with apparent gastrointestinal bleeding, leading to a diagnosis of autoimmune pathology. The aim is to highlight the importance of a comprehensive approach to pathologies in functional geriatric patients. Patients and Methods: A female patient in the seventh decade of life, housewife, with reference to unspecified leukemia in hereditary family history. Denies having tattoos. In her past medical history, the only notable are a cholecystectomy performed 25 years ago without complications and a right breast cyst resection done 30 years ago with histopathological study negative for malignancy. Denies alcohol consumption, denies history of blood transfusion, and no use of non-steroidal anti-inflammatory drugs. With cervico-vaginal cytology performed 4 months ago with a normal report. Functional and independent for activities of daily living, with depressive disorder associated with recent unresolved grief, unestimated weight loss in the last 2 years.She attends a geriatric outpatient consultation due to sporadic episodes of evacuations with melenic characteristics starting 3 months ago, with the last episode occurring 3 weeks prior. Denies episodes of epistaxis, gingival bleeding, abnormal uterine bleeding, petechiae, or bruises; denies night sweats or fever; presents to medical evaluation with evidence of unspecified-grade anemia; iron and folic acid oral supplementation is initiated. In our service consultation, hemoglobin is reported as 5 g/dl, leading to the decision for admission for further management. Results: Endoscopy was performed with a report of upper esophageal varices descending to the distal third. Management continues with a joint approach with the Gastroenterology service. Serologies for hepatitis C and B viruses are negative, liver function tests show a cholestatic pattern, and a CT scan reveals reactive changes in the liver as well as splenomegaly. Due to the absence of risk factors, a comprehensive approach for autoimmune hepatitis is initiated, with positive antinuclear and anti-mitochondrial antibodies at a titer of 1:3200, IgG 4734, IgM 887, and anti-SP100 224. Hepatic Doppler ultrasound with elastography shows moderate fibrosis (Metavir score 3). Liver biopsy reports portal lymphoplasmacytic hepatitis with damage to the limiting plate, ductular proliferation, intense lobular damage (binucleation, ballooning, and hepatocyte degeneration), and portal fibrosis (F1). Based on this, a diagnosis of autoimmune hepatitis with overlap of primary biliary cholangitis is made, and targeted management is initiated. Conclusions: Emphasizing the importance of continuing to address pathologies in patients regardless of age group and in an interdisciplinary manner is crucial. In our study population, functionality in basic and instrumental activities of daily living plays a significant role.